Staphylinidae and Nitidulidae (Coleoptera) associated with inflorescences of Etlingera elatior (Zingiberaceae) - LÓPEZ-GARCÍA, MARGARITA M.; MÉNDEZ-ROJAS, DIANA M.; GARCÍA-CÁRDENAS, ROCÍO (Revista Colombiana de Entomología, 2011)
Staphylinid and nitidulid fauna associated with Etlingeraelatior inflorescences was characterized, in relation to their senescence. 322 rove beetles belonging to five subfamilies and 28 morphospecies were collected; and 301 nitidulids belonging to two subfamilies and eight morphospecies were found. The most abundant genera were Colopterus and Coproporus. Staphylinidae was more diverse than Nitidulidae in terms of community structure. There were not statistically significant differences in abundance and richness of each subfamily among senescence stages. Rove beetles were opportunists and casual visitors taking advantage of resources that inflorescences of E. elatior offer; while sap beetles showed a stronger association between their life cycles and this plant.